Chemical–Physical Characterization of PET-G-Based Material for Orthodontic Use: Preliminary Evaluation of micro-Raman Analysis - Nicita, Fabiana; D'Amico, Cesare; Filardi, Vincenzo; Spadaro, Donatella; Aquilio, Emidio; Mancini, Maura; Fiorillo, Luca (European Journal of Dentistry, 2023)
Objectives Orthodontic treatment with clear thermoplastic aligners is in great demand by patients especially for aesthetics. Any alterations in the chemical composition of the thermoplastic material for aligners, subjected to the oral environment and exposure to various commonly used substances, could influence the desired orthodontic movement decreasing the predictability of the treatment. The objective of this study was to determine the chemical–physical characterization by micro-Raman spectroscopy of a thermoplastic material based on polyethylene terephthalate glycol (PET-G) used for the manufacture of Lineo aligners (Micerium Lab, Avegno, Italy) subjected to different staining beverages and cleaning agents.Materials and Methods Twenty-two thermoformed PET-G samples were immersed to various substances of daily use for 10 and 15 days (coffee, tea, Coca-Cola, red wine, colloidal silver disinfectant, nicotine, artificial saliva, cigarette smoke, and different combinations of saliva with some of the previous solutions). Subsequently, the chemical–physical characterization was investigated by micro-Raman spectroscopy.Results The analysis of the spectra acquired for all the specimens showed no difference in the exposure to the different solvents at 10 and 15 days. Furthermore, having ascertained the heterogeneous surface morphology of the PET-G material due to thermoforming, various deposits were present on all the samples whose consistency and concentration depended on the substance used.Conclusion The spectroscopic investigations have provided a precise and detailed analysis of the qualitative and structural data of the PET-G material under examination. No significant structural modifications of the thermoplastic polymer were found after immersion in different solutions in the exposure times adopted.
Keywords: clear aligners; PET-G; thermoplastic materials; staining substances; chemical–physical characterization; micro-Raman spectroscopy.